Neuronal remapping and circuit persistence in economic decisions - Xie, Jue; Padoa-Schioppa, Camillo (Nature neuroscience, 2016)
Different neurons in orbitofrontal cortex encode the input and the output of economic decisions. The authors demonstrate that this neural circuit is both stable and flexible. When different goods are available for choice, individual neurons adapt to the new behavioral context while preserving their function in the decision circuit. The orbitofrontal cortex plays a central role in good-based economic decisions. When subjects make choices, neurons in this region represent the identities and values of offered and chosen goods. Notably, choices in different behavioral contexts may involve a potentially infinite variety of goods. Thus a fundamental question concerns the stability versus flexibility of the decision circuit. Here we show in rhesus monkeys that neurons encoding the identity or the subjective value of particular goods in a given context 'remap' and become associated with different goods when the context changes. At the same time, the overall organization of the decision circuit and the function of individual cells remain stable across contexts. In particular, two neurons supporting the same decision in one context also support the same decision in different contexts. These results demonstrate how the same neural circuit can underlie economic decisions involving a large variety of goods.